2000
DOI: 10.1291/hypres.23.371
|View full text |Cite
|
Sign up to set email alerts
|

Relation between Left Ventricular Geometric Alteration and Extracardiac Target Organ Damage in Hypertensive Patients.

Abstract: To study the relation between left ventricular geometric alteration and extracardiac target organ damage in hypertensive patients. A retrospective study of 298 patients with essential hypertension was performed.Left ventricular mass index (LVMI) and relative wall thickness (RWT) were calculated using echocardiographic data. Patients were divided into four groups based on their left ventricular geometric pattern as determined using LVMI and RWT. Each of the four left ventricular geometric patterns was associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Westerhof et al 14 held the view that patients with concentric remodeling and concentric hypertrophy have higher mortality than those with eccentric hypertrophy and normal morphologic characteristics. However, several studies demonstrated that eccentric hypertrophy is more highly related to deleterious cardiovascular outcomes 15 17 and was associated strongly with decreased systolic and diastolic function 18 . We hypothesized that some wave intensity parameters in eccentric hypertrophy were significantly different than those found in other geometric patterns.…”
Section: Discussionmentioning
confidence: 93%
“…Westerhof et al 14 held the view that patients with concentric remodeling and concentric hypertrophy have higher mortality than those with eccentric hypertrophy and normal morphologic characteristics. However, several studies demonstrated that eccentric hypertrophy is more highly related to deleterious cardiovascular outcomes 15 17 and was associated strongly with decreased systolic and diastolic function 18 . We hypothesized that some wave intensity parameters in eccentric hypertrophy were significantly different than those found in other geometric patterns.…”
Section: Discussionmentioning
confidence: 93%
“…Target organ damage was found to be higher among patients with increased LVMI as compared to those with normal LVMI, with p<0.01 for retinopathy. Ding Y et al 16 showed that there is extremely high prevalence of retinopathy in patients with increased left ventricular mass index (p<0. 05).…”
Section: Discussionmentioning
confidence: 99%
“…The classification of LV geometry (normal, concentric remodeling, eccentric hypertrophy, and CH) based on LVMI and RWT has been widely used in population studies. 5 , 6 , 9) Of the four types of LV geometry, a previous study showed that CH presented with the highest SBP and was considered to be related to hypertension. 5 , 6) CH is induced by pressure overload, 17) such as hypertension, aortic stenosis, hypertrophic cardiomyopathy, and storage diseases, among others, while LVH was classically considered to be the result of hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…We focused on only CH as an indicator of LVH since it was known to be the most strongly associated with hypertension out of the four types of LV geometry. 5 , 6) Patients’ history, including systolic blood pressure (SBP) just before admission without the intravenous administration of an antihypertensive drug, and factors associated with atherosclerosis, were compared between those with types A or B AD. In addition, the following data regarding LV geometry as measured by echocardiography were compared between such patients: days from the onset of AD to evaluations with echocardiography, left ventricular end-diastolic dimension (LVDd), left ventricular end-systolic dimension (LVDs), left ventricular ejection fraction (LVEF), values of LVMI in total, those in males (mLVMI), those in females (fLVMI), the value of RWT, the prevalence of increased LVMI, the prevalence of increased RWT, and the prevalence of CH.…”
Section: Methodsmentioning
confidence: 99%